Effect of rice residue management practices and irrigation regimes on root mass density and water productivity of wheat in rice-wheat system in Northern region of India - KUMAR, MUKESH; SINGH, JAGDISH; SHARMA, SEEMA; CHHINA, R.S. (Journal of Soil and Water Conservation, 2025)
The field study was conducted to evaluate soil physical properties, root activity, crop yield, water use and water productivity under five tillage-residue management practices namely conventional tillage (RRC), no-tillage without residue (RRZ), happy seeder (HS) with surface residue retention, residue incorporation with superseeder (SS) and soil inversion along with residue by mould board plough (MMC) and three irrigation regime IW/CPE (Irrigation water/Cumulative pan evaporation) ratio 0.9 (I1), 0.6 (I2) and 0.3 (I3). The soil bulk density (Mg m-3) was found to be significantly higher under HS (1.42) and RRZ (1.42) followed by RRC (1.38), SS (1.35) and least under MMC (1.31) in 0-15 cm soil depth. Similar trend was also observed in 15-30 cm soil depth. The soil organic carbon (SOC) (g kg-1) was found to be highest under SS (5.34) and lowest under RRC (4.61) at the surface layer due to addition of organic matter in soil under SS. The moisture storage (cm) (up to 90 cm soil depth) was found significantly higher under I1 (10.40) as compared to I2 (9.48) and I3 (9.15) due to increase in number of irrigations. Root mass density (RMD) declined sharply with increase in soil depth. In 0-15 cm layer, mean maximum RMD was found under MMC and minimum under RRZ. Similar trend was observed at all the soil depths up to 60 cm. The wheat grain yield (t ha-1) was observed maximum in I1 (5.56) followed by I2 (5.22) and I3 (5.19). The water use efficiency (kg ha-1 mm-1) was found maximum under I3 (12.69) which was at par with I2 (12.66) and minimum under I1 (11.65). Happy seeder (HS) as well as the residue incorporation with rotavator (SS), in terms of sustainability, quantified by the soil properties studied, thus proved to be superior compared to other tillage practices.